Dating the 'app' way - Tan, Michelle Yi Ying (2018)
The dating realm has gone through a digital transformation as more engage the use of mobile dating applications to expand their romantic network. Despite its increasing popularity, dating applications have a reputation for casual dating and ‘hook-ups’ only. This spells disquieting news for Singapore as singles delay finding a lifelong partner and subsequently, marriage and childbearing. Through this paper, we attempt to analyse how dating applications impact the quality of interactions between mixed mode romantic partners and subsequently, commitment levels of couples from dating applications. Our study suggests most view the dating application as a tool to expand their social circle but date with a flippant attitude. This cultivates a ‘ghosting’ culture, leading one to develop alternative personas and become superficial in their interactions. Despite this, Singaporeans remain deeply entrenched and committed in their mixed-mode relationships; they establish long-term commitment goals, discontinue use of dating apps and retain a sense of exclusivity with one another.